Pengukuran dan Faktor Kualitas Hidup pada Orang Usia Lanjut - Indra Yohanes Kiling; Beatriks Novianti Kiling-Bunga (Journal of Health and Behavioral Science, 2019)
Older people are a group of people that are struggling in the last phase of their life. In this phase, a person faces various challenges to fulfill their needs to get a life with quality. High level of quality of life is something that is subjective, mostly different in each person. This paperis a literature review that will discuss factors related to quality of life by reviewing existing relevant literatures. Indicators and measurement tools will also be discussed in this paper. Quality of life factors that bceome the main reference in the global context are the one stated byWorld Health Organization. These factors would also influence scales that measure quality of life, which in turn were further developed to fit specific cultural context to fulfill the needs of each unique population. Indicators of quality of life were concluded as influenced by varioussituations in a person’s life including environment, culture and beliefs. The content hopefully will be able to provide knowledge concerning quality of life in relations with elderly. Understanding the concept of quality of life would help to advance the literature including in it well-being and other related concepts.